2014
DOI: 10.1177/0883073813513333
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Short Interval Cortical Inhibition Correlates With Atomoxetine Response in Children With Attention-Deficit Hyperactivity Disorder (ADHD)

Abstract: Clinical trials in children with Attention Deficit Hyperactivity Disorder (ADHD) show variability in behavioral responses to the selective norepinephrine reuptake inhibitor atomoxetine (ATX). The objective of this study was to determine whether Transcranial Magnetic Stimulation (TMS)-evoked Short Interval Cortical Inhibition (SICI) might be a biomarker predicting, or correlating with, clinical ATX response. At baseline and after 4 weeks of ATX treatment in 7–12 year old children with ADHD, TMS-SICI was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The fALFF effect of atomoxetine treatment associated with clinical improvement emphasized the importance of using resting-state functional MRI (RS-fMRI) techniques to exploring the medication effects on intrinsic brain activity in children with ADHD. Children ages 7–12 years with ADHD who respond clinically to atomoxetine had improvements of clinical symptoms, correlated with a decrease in motor cortex short interval cortical inhibition ( 40 ). A randomized, double-blind, placebo-controlled, crossover study ( 13 ) shows that atomoxetine upregulates inferior frontal activation and improves DMN deactivation during cognitive functions, improves attention functions and upregulates abnormal fronto-cortical activation during executive function tasks in ADHD patients, and appears to have drug-specific effects of up-regulating DLPFC.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fALFF effect of atomoxetine treatment associated with clinical improvement emphasized the importance of using resting-state functional MRI (RS-fMRI) techniques to exploring the medication effects on intrinsic brain activity in children with ADHD. Children ages 7–12 years with ADHD who respond clinically to atomoxetine had improvements of clinical symptoms, correlated with a decrease in motor cortex short interval cortical inhibition ( 40 ). A randomized, double-blind, placebo-controlled, crossover study ( 13 ) shows that atomoxetine upregulates inferior frontal activation and improves DMN deactivation during cognitive functions, improves attention functions and upregulates abnormal fronto-cortical activation during executive function tasks in ADHD patients, and appears to have drug-specific effects of up-regulating DLPFC.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Fortunately the progress of human brain imaging studies in recent years has provided us with new insights into the ADHD management with atomoxetine (10,13,(38)(39)(40). The right inferior PFC is a key area of dysfunction in ADHD during inhibitory performance (41).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“… 10 Prior paired-pulse-TMS studies have shown that ADHD children have reduced SICI, 11 , 12 that greater ADHD severity correlates with more reduced SICI, 12 , 13 and that ADHD medications affect SICI. 14 , 15 In functional-TMS , administering TMS during performance of a functional circuit that includes M1 may up-modulate MEP amplitudes, 16 , 17 which we term ‘Task-Related Up-Modulation’ (TRUM). Prior functional-TMS studies have shown that ADHD children have reduced TRUM during a response inhibition task.…”
Section: Introductionmentioning
confidence: 99%